2023
DOI: 10.1007/s12011-023-03633-z
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and Organic Selenium Speciation of Seleno-Yeasts Used as Feed Additives: New Insights from Elemental Selenium Determination

Abstract: Seleno-Yeasts (SY) used as feed additives are known to contain different Selenium (Se) species. Seleno-Yeasts has been shown, on previous analytical methods, to contain selenomethionine (SeMet), selenocysteine (SeCys), selenate (SeIV) and selenite (SeVI), and various other organic and inorganic Se forms identified but rarely quantified. A new advanced method has allowed elemental Se (Se0), an inorganic Se species, to be quantified, thereby obtaining better insight into the proportion of inorganic Se in SY prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“… Davis and Fear (1996) suggested that different selenium forms can influence the distribution and deposition of selenium between the yolk and albumen. SY, being a fermentation product, predominantly contains selenium in the form of selenomethionine (60–84%), but it also contains selenium in various organic and inorganic forms such as selenocysteine, selenate and selenite, whereas the absorption and metabolism mechanisms of many selenium compounds are not yet fully understood ( LeBlanc and Mester, 2021 ; Hachemi et al, 2023 ). Hence, this discrepancy in selenium deposition between SM and SY in the yolk and albumen may be attributed, at least in part, to these factors.…”
Section: Discussionmentioning
confidence: 99%
“… Davis and Fear (1996) suggested that different selenium forms can influence the distribution and deposition of selenium between the yolk and albumen. SY, being a fermentation product, predominantly contains selenium in the form of selenomethionine (60–84%), but it also contains selenium in various organic and inorganic forms such as selenocysteine, selenate and selenite, whereas the absorption and metabolism mechanisms of many selenium compounds are not yet fully understood ( LeBlanc and Mester, 2021 ; Hachemi et al, 2023 ). Hence, this discrepancy in selenium deposition between SM and SY in the yolk and albumen may be attributed, at least in part, to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential reason is the high bioavailability of OH‐SeMet, as the chemical structure of OH‐SeMet is very similar to methionine, and Met‐tRNA cannot distinguish between methionine and OH‐SeMet. This allows OH‐SeMet to combine directly with proteins in the body, and be used as a source of Se (Hachemi et al, 2023 ). It has been suggested that higher expression of selenoprotein may better demonstrate the nutritional status and metabolic function of Se (Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%